Ironi Sampah dan Pariwisata: Respon Multiaktor atas Krisis Sampah di Kawasan Wisata Kaliurang - Mulyasari, Runavia; Widyawati, Vania Sekar (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2025)
The massive development of tourism in the Kaliurang area of Yogyakarta over several decades has had a significant impact on environmental changes, both physical and non-physical. One of the impacts felt as a result of the massive tourism activities in the Kaliurang area is waste. The waste produced by tourists from various tourist activities in the Kaliurang area every day is voluminous, in addition to the waste produced by the local community. Unfortunately, tourism operators leave waste management and handling to the village government, which has a limited management system. This situation has persisted for years, leading to waste accumulation. In 2025, the local government, together with BUMKal, attempted to address the existing waste crisis by establishing a Waste Management House (RPS) with a digital system. This governance requires multi-actor cooperation (government, tourism operators, and local communities) to overcome the waste crisis through cross-actor collaboration. The responses that emerge from the interaction of these three actors can be categorised into four types, namely structural responses, socio-cultural responses, technological and innovative responses, and economic responses. The formalisation of waste institutions is not only a solution to poor waste management systems but also a new, more systematic governance model for environmental and socio-cultural welfare for multiple actors in the Kaliurang tourism area.